As acrobacias de um novo escritor de filosofia: Fichte sobre a lógica de Hegel - Ferraguto, Federico (Revista Eletrônica Estudos Hegelianos, 2017)
ABSTRACT: The paper aims to clarify some elements involved in Fichte’s interpretation of Hegel's Science of Logic, as it appears in an excerpt from the first course of transcendental logic taught by Fichte in the summer semester of 1812. My claim is that both Fichte and Hegel develop their reflections on logic in order to solve two problems: to rethink and justify the Kantian concept of ‘transcendental’ and to connect this justification to the definition of a principle that allows to account for the structure of reality and for the knowledge by which reality is constituted as such. In § 1 I will present the general requirements that make it necessary to construct a science of logic, in § 2 I analyze Fichte’s criticism of Hegel. In sections 3-5 I justify my interpretation of Fichte, I highlight the problems involved in it, and I compare Fichte’s and Hegel’s views.